Investigating the mechanism of Echovirus 30 cell invasion - Liang, Yucai; Chen, Junbing; Wang, Congcong; Yu, Bowen; Zhang, Yong; Liu, Zhijun (Frontiers in Microbiology, 2023)
Viruses invade susceptible cells through a complex mechanism before injecting their genetic material into them. This causes direct damage to the host cell, as well as resulting in disease in the corresponding system. Echovirus type 30 (E30) is a member of the Enterovirus B group and has recently been reported to cause central nervous system (CNS) disorders, leading to viral encephalitis and viral meningitis in children.In this review, we aim to help in improving the understanding of the mechanisms of CNS diseases caused by E30 for the subsequent development of relevant drugs and vaccines.